Integrated single-cell and transcriptome sequencing data reveal the value of IL1RAP in gastric cancer microenvironment and prognosis - Yang, Weifeng; Wu, Xiaohua; Wang, Jian; Ou, Wenquan; Huang, Xing (Frontiers in Oncology, 2025)
BackgroundInvestigating the pivotal role of IL1RAP in the tumor microenvironment of gastric cancer.MethodDownload and collate transcriptomic and single-cell data from gastric cancer patients. Three machine learning algorithms identified distinct sets of prognostic genes in gastric cancer patients. The CIBERSORT and ssGSEA algorithms elucidated immune infiltration patterns, while TIDE and TCGA predicted immune-related outcomes. Furthermore, single-cell sequencing data confirmed the interaction of IL1RAP within the tumor microenvironment. Finally, differential expression levels of IL1RAP protein and mRNA were validated.ResultAfter machine learning screening and independent dataset validation, high IL1RAP expression was identified as a poor prognostic factor for gastric cancer patients. Immune infiltration analysis indicated that the low IL1RAP expression group was associated with higher infiltration of CD8+ T cells and M1-type macrophages, whereas the high IL1RAP expression group exhibited increased presence of M2-type macrophages. Immunotherapy prediction models suggested a more favorable response to PD-1 treatment in the low IL1RAP expression group. Prognostic models incorporating IL1RAP demonstrated superior predictive performance. Single-cell data analysis revealed that IL1RAP plays a critical role in regulating intercellular communication within the tumor microenvironment. Our findings were further validated by confirming elevated IL1RAP expression levels in gastric cancer tissues.ConclusionIL1RAP plays a critical role in the tumor microenvironment of gastric cancer and serves as a robust predictor of immunotherapy efficacy in gastric cancer.